2017
DOI: 10.3390/ijms18050927
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Expression Profiling of the Auxin Response Factors in Dendrobium officinale under Abiotic Stresses

Abstract: Auxin response factor (ARF) proteins play roles in plant responses to diverse environmental stresses by binding specifically to the auxin response element in the promoters of target genes. Using our latest public Dendrobium transcriptomes, a comprehensive characterization and analysis of 14 DnARF genes were performed. Three selected DnARFs, including DnARF1, DnARF4, and DnARF6, were confirmed to be nuclear proteins according to their transient expression in epidermal cells of Nicotiana benthamiana leaves. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 57 publications
3
19
0
Order By: Relevance
“…Several studies have allowed the identification of the role of some of the 23 ARFs and 29 Aux/IAAs in the presence of auxins at different stages of plant development, using mutants of loss or gain of function in A. thaliana (Liscum & Reed, 2002). To mention a few, ARF5 is critical for the formation of the embryonary axis and the embryogenic root, and the development of the flowers, as well as part of the vascular tissue; ARF6 acts in the maturation of the flowers and, in tomato, ARF9 regulates cell division (Li et al, 2015; Li et al, 2016; Weijers & Wagner, 2016; Chen et al, 2017). Regarding Aux/IAA proteins, studies in A. thaliana have shown that mutations in the Aux/IAA7 gene produce short hypocotyl phenotypes and deformities in the leaves; mutations in the Aux/IAA12 gene cause root abnormalities (Liscum & Reed, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have allowed the identification of the role of some of the 23 ARFs and 29 Aux/IAAs in the presence of auxins at different stages of plant development, using mutants of loss or gain of function in A. thaliana (Liscum & Reed, 2002). To mention a few, ARF5 is critical for the formation of the embryonary axis and the embryogenic root, and the development of the flowers, as well as part of the vascular tissue; ARF6 acts in the maturation of the flowers and, in tomato, ARF9 regulates cell division (Li et al, 2015; Li et al, 2016; Weijers & Wagner, 2016; Chen et al, 2017). Regarding Aux/IAA proteins, studies in A. thaliana have shown that mutations in the Aux/IAA7 gene produce short hypocotyl phenotypes and deformities in the leaves; mutations in the Aux/IAA12 gene cause root abnormalities (Liscum & Reed, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Phytohormones are involved in the responses of various plants to environmental stimuli and stress by altering the expression levels of many ARF genes [ 6 , 51 ]. However, evaluation of pepper’s adaptability to its environment is very limited.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have allowed the identification of the role of some of the 23 ARFs and 29 Aux/IAAs in the presence of auxins at different stages of plant development, using mutants of loss or gain of function in A. thaliana (Liscum & Reed 2002). To mention a few, ARF5 is critical for the formation of the embryonary axis and the embryogenic root, and the development of the flowers, as well as part of the vascular tissue; ARF6 acts in the maturation of the flowers and, in tomato, ARF9 regulates cell division (Li et al, 2015;Weijers & Wagner 2016;Chen et al, 2017). Regarding Aux/IAA proteins, studies in A. thaliana have shown that mutations in the Aux/IAA7 gene produce short hypocotyl phenotypes and deformities in the leaves; mutations in the Aux/IAA12 gene cause root abnormalities (Liscum & Reed 2002).…”
Section: Discussionmentioning
confidence: 99%